Estruturas de madeira e de aço para telhados: vantagens e desvantagens do uso na engenharia civil - Diniz, Daniel Pontes Vieira (Universidade Federal Rural do Semi-Árido, 2018)
Steel as a raw material for civil construction has been gaining global connotation for some time, in Brazil it would not be different, especially when it is remembered that the country is the eighth largest producer of steel in the world, steel industries are increasingly more transporting new technologies and increasing the level of quality, also contributing to the preservation of native forests, since, in addition to the decrease in the use of wood, which is still the main raw material used in the use of roofs in civil construction, steel is still a 100% recyclable material, thus becoming a competitive candidate in the construction of roof structures. But, on the other hand, wood is still full of tradition, besides being the most conventional form, it is easy to find skilled labor to perform a good installation work, always seeking to employ new species and new components produced in laboratories. It is concluded that the use of steel in roof structures is advantageous in relation to the use of wood in the same.
Monografia
Keywords: Construção civil; Aço; Madeira; Telhado; Civil construction; Stainless steel; Roof; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA